IMPLEMENTATION OF COOPERATION BETWEEN THE SYNERGY FOUNDATION AND THE BAITUL MAL PLN FOUNDATION IN BANYUWANGI REGENCY - Riany Laila Nurwulan; Uga Pratama Gunawan (SEAN Institute, 2023)
This research aims to find out how the cooperation between the Sinergi Foundation and YBM PLN is implemented in channeling people's funds by the Sinergi Foundation which includes the models, strategies, and program implementation schemes that are carried out. Sinergi Foundation (SF) is an independent institution concerned with encouraging the development of creativity and innovation in Social-Empowerment based on Productive Waqf and ZIS (Zakat, Infaq- Alms). The research method used in this study is a qualitative research method with a case study approach at the Synergy Foundation, Bandung City. The results of this study indicate that SF is implementing a community empowerment program with YBM PLN in Banyuwangi Regency. The collaboration model built by SF and YBM PLN is a partnership in which SF and YBM PLN jointly develop and implement community empowerment programs for fishing communities in Banyuwangi Regency. The strategy implemented by SF in carrying out its partnership program includes four aspects, namely (1) the existence of guidelines and codes of conduct; (2) the existence of corporate management systems and policies; (3) corporate leadership strategy in partnerships; (4) as well as commitment and partnership among stakeholders. And the implementation scheme The implementation scheme of the Partnership by SF and partners focuses on community empowerment in order to create a better life for the target community and their environment. In addition, SF and YBM PLN also focus on preserving the environment and building tourism villages in the future which are expected to have a positive impact on the community.